2001
DOI: 10.1063/1.1347964
|View full text |Cite
|
Sign up to set email alerts
|

Electron attachment to CF3Cl and CH3Cl on the surface and in the bulk of solid Kr

Abstract: The formation of stable anions induced by the impact of 0–1.6 eV electrons on CF3Cl and CH3Cl condensed at the surface, and embedded within the bulk of solid Kr is investigated by measuring charging of the doped Kr films. Effects of the Pt substrate and under- and over-layer coverage of these molecules on the dissociative electron attachment and stable anion formation (SAF) are studied in detail by varying the film thickness and the position of the molecules within the film. Due to recent advances, we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 57 publications
2
46
1
Order By: Relevance
“…These values are more than two orders of magnitudes higher than the equivalent DEA cross section in the gas phase. 25 One may conclude that there is an interplay between stabilization effects and escape probability from a cage of the dissociated fragments that dictates the net probability for the DEA process of an embedded CH 3 Br molecule. Voids in the amorphous solid that reduce the perfect cage structure may also reduce the cage effect in favor of enhancing DEA.…”
Section: Multilayer Film Irradiated At 82 Kmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are more than two orders of magnitudes higher than the equivalent DEA cross section in the gas phase. 25 One may conclude that there is an interplay between stabilization effects and escape probability from a cage of the dissociated fragments that dictates the net probability for the DEA process of an embedded CH 3 Br molecule. Voids in the amorphous solid that reduce the perfect cage structure may also reduce the cage effect in favor of enhancing DEA.…”
Section: Multilayer Film Irradiated At 82 Kmentioning
confidence: 99%
“…2,6,25 These ions generate electric field around them and are attracted to their image charge inside the bulk metal underneath. To caracterize the dissociation products embedded inside the multilayer structure after irradiation and to probe the multilayer restructure during the diffusion of the Br -ions, a set of ∆ -TPD spectra were recorded under similar condition as for the ∆p-TPD.…”
Section: ∆ -Tpdmentioning
confidence: 99%
“…Studies in this field have included inter-and intramolecular electron transfer, 6 transmission 7-9 conduction within and through molecules, 10,11 and dissociative electron attachment (DEA) processes. [12][13][14] Recent interest in molecular electronics has brought the basic science in this field closer to modern technology than ever before. [8][9][10][11] Here we present, for the first time, the phenomenon of molecular orientation dependent electron-molecule interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The conceptually simplest such environment may well be with target molecules embedded in a rare gas lattice. In two tour de force experiments, Nagesha and Sanche 1 and Fabrikant et al 2 reported absolute cross sections for production of stable negative ions in CF 3 Cl and CH 3 Cl, respectively, within a solid lattice of krypton. In more recent work, 3 these authors have reported new and more reliable values of the absolute cross sections for these two species both within and on the surface of the rare gas film.…”
Section: Introductionmentioning
confidence: 99%
“…In two tour de force experiments, Nagesha and Sanche 1 and Fabrikant et al 2 reported absolute cross sections for production of stable negative ions in CF 3 Cl and CH 3 Cl, respectively, within a solid lattice of krypton. In more recent work, 3 these authors have reported new and more reliable values of the absolute cross sections for these two species both within and on the surface of the rare gas film. The measurements were accompanied 2,3 by theoretical DEA cross sections obtained by using a semiempirical R-matrix method 4 extended to incorporate the effects of the condensed matter environment.…”
Section: Introductionmentioning
confidence: 99%